Correction: COVID-19 vaccine effectiveness among South Asians in Canada. - Rahul Chanchlani; Baiju R Shah; Shrikant I Bangdiwala; Russell J de Souza; Jin Luo; Shelly Bolotin; Dawn M E Bowdish; Dipika Desai; Karl Everett; Scott A Lear; Mark Loeb; Zubin Punthakee; et al. (PLOS Global Public Health)
[This corrects the article DOI: 10.1371/journal.pgph.0003490.].